(untitled) (Revista Latino-Americana de Enfermagem, 2009)
Content analysis comprises a set of techniques for organizing communication/information - a procedure used with qualitative data to make themes/topics and concepts/knowledge emerge. Communication content, considering human written or spoken discourse, is complex and presents valuable polysemous characteristic. With the dissemination of the clinical-qualitative method, the use of content analysis, considered an important methodological tool, raises theoretical-practical issues that need to be taken into consideration for its academically precise use. Thus, this article aimed to enumerate specific elements of the content analysis technique and discuss its suitability for the clinical-qualitative method that combines generic qualitative methods from Human and Cultural Sciences with the area of Health Sciences. Concepts were selected due to their pertinence, use and eventual adaptation to the method focused on.